Grammar at work for college freshmen - Opetina, Leandro N. (Manila, Philippines, 2007)
This book, Grammar at Work, is designed to hone the listening, speaking, writing and reading skills of the learners via grammar. There are exercises for the learners to grapple with before they enter or leave the realm of grammar. And in order for the students to savor the sweet twist of English, idiomatic expressions come along
Keywords: English language- Grammar